About unrenowned crusade of Mongols to Yenisei in 1207 - Zoriktuev, Bulat R. (The New Research of Tuva, 2013)
Article present the results of study about little-known and little-studied episode of early Mongolian conquest in 1207 when Mongols initiated a crusade to conquer woodland people.
Keywords: conquest of Jochi; Oirat Khudukha-Beki; Shikshit; Tuva; Yenisei Kyrgyzs